Motor function of central nervous system - Tykhonovska, M. A.; Sukhomlinova, I. Ye.; Ivanchenko, D. G.; Tykhonovsky, O. V.; Тихоновська, Марина Анатоліївна; Сухомлінова, Ірина Євгенівна; Іванченко, Дмитро Григорович; Тихоновський, Олександр Володимирович (Zaporizhzhia state medical university, 2018)
Methodical recommendations compiled in accordance with the program of "normal physiology". Guidelines are intended to help students prepare for practical classes and learn the material. Can be used for training of 2th-years students of international faculty, discipline "normal physiology". This manual is recommended for II year students of International Faculty of specialty "General medicine" studying biological chemistry, as additional material to prepare for practical training and licensing exam "KROK 1: General medical training".
Моторні функції центральної нервової системи